Boris Ilyich Alperovich (to the 80th birthday) - Editorial Article (Бюллетень сибирской медицины, 2007)
Creative biography of the known Russian surgeon and scientist - doctor of medical sciences, Honoured Physician of Russia, Honoured Science Worker of Russia, State Prize Winner of RF, Honourary Citizen of Tomsk , professor B.I. Alperovich is presented in the article